Passive Investing and the Rise of Mega-Firms - Jiang, Hao; Vayanos, Dimitri; Zheng, Lu (Review of Financial Studies, 2025)
Abstract We study how passive investing affects asset prices. Flows into passive funds disproportionately raise the stock prices of the economy’s largest firms, especially those large firms in high demand by noise traders. Because of this effect, the aggregate market can rise even when flows are entirely due to investors switching from active to passive funds. Intuitively, passive flows increase the idiosyncratic risk of large firms in high demand, which discourages investors from correcting the flows’ effects on prices. Consistent with our theory, prices and idiosyncratic volatilities of the largest S&P500 firms rise the most following flows into that index.